Effects of Chinese opera on the reproductions of Ibsen’s plays - LAU, Miriam Leung Che (Nordlit, 2015)
As part of a globalized phenomenon, the reproductions of Ibsen’s plays on the Chinese theatrical stage increasingly focus upon the exploration and expansion of new cultural forms, as Patrice Pavis defines interculturalism as “grasping the dialectical of exchanges of civilities between cultures”. However, how do we evaluate the effectiveness of the many “intercultural” productions that surround us today? I attempt to answer this question by comparing two Chinese reproductions of Ibsen’s plays that employ elements of Chinese opera on varying scales. The first one is a total transformation of Hedda Gabler into a Hangzhou yue opera form, Xin Bi Tian Gao (Aspirations Higher than the Sky, 心比天高) in 2006. As part of the yue opera tradition, Hedda Gabler was staged in an all-female cast. The second one is a fragmented insertion of a Peking opera excerpt into the staging of A Doll’s House by the National Experimental Theatre of China in 1998. One of the highlights of the play is a Norwegian actress, who plays Nora, singing and dancing a short Peking opera excerpt, thus replacing the tarantella dance in the original play. Contextualising the multiple perspectives towards interculturalism by Patrice Pavis, Richard Schechner and Rustom Bharucha, I aim to explore how the appropriation of Chinese opera in such performances might strengthen or weaken the reciprocal flows between the source and target cultures in Pavis’s “hourglass model”, and whether the initial attempt of revitalising both Chinese and Western art forms has backfired and misproduced Bertolt Brecht’s alienation effect directed at the contemporary audience.